Synthetic human seminal alpha-inhibin-92 selectively suppresses follicle-stimulating hormone release in vivo. - Yu, W H (1988)
A 92-amino acid polypeptide, alpha-inhibin-92 (alpha-IB-92), has been isolated and characterized from human seminal plasma and found to be active in suppressing follicle-stimulating hormone (FSH) release in vitro. In the present in vivo study, intravenous injection of synthetic alpha-IB-92 (4 and 20 micrograms) significantly suppressed FSH release (P less than 0.001), whereas this peptide had no effect on luteinizing hormone (LH) release in 1-day orchidectomized male rats. In contrast, third ventricular injection of alpha-IB-92 (0.02, 0.4, 4, or 20 micrograms) had no effect on FSH and LH release in 1- or 2-day orchidectomized rats. These results indicate that alpha-IB-92 exerts a FSH suppressing activity by direct action on the pituitary gland.